Weighing sensor manufacturing method based on conductive carbon fiber

By using inorganic filling materials and high-temperature oxidation activated carbon fiber powder in the force sensor, the problem of high noise and temperature sensitivity of the sensor output signal is solved, achieving a more stable signal output and cost-reducing effect.

CN119756537APending Publication Date: 2025-04-04CHANGZHOU TEXTILE GARMENT INST
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510110119.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing force sensors made of conductive inks based on carbon materials have high output signal noise, are sensitive to temperature, and are easily affected by the external environment, resulting in unstable output signal.

Method used

Inorganic filler materials are used instead of organic polymer filler materials to form a new carbon fiber powder resistance slurry, and the activated carbon fiber powder is more closely combined with the inorganic filler material through high-temperature oxidation, and a strain resistance wire grid is prepared to form a measurement bridge for weighing sensors.

Benefits of technology

The stability of the sensor output signal is improved, the sensitivity to temperature is reduced, and the stability of the signal is enhanced. It is larger than that of the metal strain gauge sensor, and the cost, complexity and volume are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119756537A_ABST
    Figure CN119756537A_ABST
Patent Text Reader

Abstract

The invention discloses a method for manufacturing a weighing sensor based on conductive carbon fibers, which comprises the following steps of: preparing carbon fiber powder by using carbon fiber monofilaments, preparing carbon fiber resistance slurry with proper viscosity from the obtained carbon fiber powder, coating and printing the carbon fiber resistance slurry on the surface of cured glass to prepare a strain resistance wire grid, and preparing the weighing sensor based on the conductive carbon fibers. According to the invention, an inorganic filling material is adopted to replace an organic polymer filling material, new carbon fiber powder resistance paste is formed, carbon fiber powder is oxidized and activated at a high temperature, and the carbon fiber powder is combined with the inorganic filling material more tightly in the sintering process, so that the resistance of the carbon fiber powder is improved. And the inorganic filling material is similar to the glass substrate material, the resistor bonding is firmer, the output signal of the sensor is larger than that of a metal strain gauge sensor, and the signal stability is improved compared with that of a carbon-based ink product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of weighing sensors, and in particular relates to a manufacturing method of a weighing sensor based on conductive carbon fiber. Background Art

[0002] A weighing sensor is actually a device that converts mass signals into measurable electrical signal outputs. When using a sensor, the actual working environment of the sensor should be considered first. This is crucial to the correct selection of a weighing sensor. It is related to whether the sensor can work properly, its safety and service life, and even the reliability and safety of the entire weighing instrument. There are qualitative differences between the old and new national standards in the basic concepts and evaluation methods of the main technical indicators of weighing sensors. There are mainly several styles, such as S-type, cantilever type, spoke type, plate ring type, diaphragm box type, bridge type, column type, etc.

[0003] With the continuous development of intelligent technology, the market has an increasing demand for accurate, sensitive and low-cost sensors. Existing weighing sensors usually use strain gauges or piezoelectric materials, but these technologies have problems such as high cost or complexity. In recent years, flexible electronic technology based on conductive ink has become a new research direction, which can achieve the development of high-performance sensors through simple manufacturing processes.

[0004] By utilizing the conductive and resistive strain properties of carbon materials, they are first mixed with other solvents to make ink, and then various force sensors can be made through printing and other processes. For example, the patent numbers in the prior art are "CN110105813A-A carbon-based conductive ink, its preparation method and use", "CN 117804326A Preparation and application of an embedded carbon nanocomposite flexible piezoresistive sensor", "CN 118516012 A Sensitive ink for high sensitivity coefficient strain gauge, sensitive ink printed strain gauge and preparation method thereof", etc., all of which describe the ink manufacturing method and its application in force measurement.

[0005] However, these force sensors made of carbon conductive ink all have a disadvantage: the sensor output signal has high noise, is sensitive to temperature, is easily affected by the external environment, and has unstable output signals. Although these can be supplemented by some temperature or zero-point compensation methods, they mostly rely on the linkage control of external temperature-sensitive components and sensor signals. These methods often increase cost, complexity or volume.

[0006] From a microscopic perspective, the signal noise of conductive ink sensors based on carbon materials (such as carbon nanotubes, graphene, graphite, etc.) mainly comes from the physical properties of the carbon materials themselves and their behavioral changes in composite materials. These changes lead to changes in the resistivity, electron mobility and microstructure of the composite materials, making the sensor more sensitive. Therefore, improving the behavioral characteristics of these carbon materials in composite materials is also one of the technical paths to improve the stability of the output signal of carbon-based material sensors. Summary of the invention

[0007] The purpose of the present invention is to provide a method for manufacturing a weighing sensor based on conductive carbon fiber. The technical problem to be solved is that the sensor output signal in the prior art has large noise, is sensitive to temperature, is easily affected by the external environment, and has unstable output signal.

[0008] To achieve the above object, the present invention provides the following technical solutions: The present invention provides a method for manufacturing a weighing sensor based on conductive carbon fiber, comprising: preparing carbon fiber powder using carbon fiber monofilament; The obtained carbon fiber powder is used to prepare a carbon fiber resistor slurry with suitable viscosity; The carbon fiber resistor slurry is printed on the solidified glass surface to prepare the strain resistor wire grid; The strain resistance wire grids are connected through wires to form a measuring bridge of the weighing sensor.

[0009] A new carbon fiber powder resistor slurry is formed by using inorganic filling materials instead of organic polymer filling materials. The carbon fiber powder is activated by oxidation at high temperature, and is more tightly combined with the inorganic filling during the sintering process. The inorganic filling and the glass substrate are the same material, so the bonding of the resistor is more firm. The output signal of the sensor is larger than that of the metal strain gauge sensor, and the signal stability is improved compared to the carbon-based ink product.

[0010] Optionally, the step of preparing carbon fiber powder using carbon fiber monofilaments specifically includes: Grinding: Grind the carbon fiber filaments into carbon fiber powder with a length not exceeding 100um; Stirring: Mix and stir the carbon fiber powder and acetone solution, and then ultrasonically vibrate for 15-30 minutes to obtain a carbon fiber solution; Vacuuming: The obtained carbon fiber solution is vacuumed and then filtered to obtain carbon fiber powder.

[0011] By mixing and stirring the carbon fiber powder with the acetone solution, the carbon fiber powder is fully dispersed in the acetone solution. Ultrasonic vibration helps to remove bubbles that may exist in the solution, improve the quality and stability of the solution, and impurities in the solution are removed by vacuuming to ensure the high purity of the carbon fiber powder.

[0012] Optionally, the obtained carbon fiber powder is used to prepare a carbon fiber resistor slurry with suitable viscosity, specifically comprising: The carbon fiber powder was placed in a glass container, distilled water was added, and the mixture was stirred and filtered. The process was repeated until the pH value of the solution was neutral. The filtered carbon fiber was placed in a heating device. The heating temperature was set to 80°C and the heating time was set to 4 hours. Impurities on the surface of the carbon fiber were removed to obtain a carbon fiber powder with a clean surface.

[0013] By placing the fiber powder in a glass container, impurities on the surface of the carbon fiber can be fully removed, making the powder drier and thus significantly improving its purity.

[0014] Optionally, 1-7 parts of clean carbon fiber powder, 2-4 parts of low-temperature lead-free glass powder, 1-2 parts of diluent, and 3-4 parts of anhydrous ethanol are mixed into a carbon fiber resistor slurry with appropriate viscosity. The use of low-temperature lead-free glass powder can not only enhance the stability of the slurry, but also improve its conductivity.

[0015] Optionally, the mixing method includes: first stirring the mixture using a magnetic stirrer at room temperature, the stirring speed is 600 revolutions per minute, the stirring time is 2-6 hours, then setting the temperature to 85 degrees, adjusting the speed to 1000 revolutions per minute, and continuing to stir until the viscosity of the carbon fiber resistor slurry reaches 5000-30000cps. The various ingredients can be fully integrated through the segmented stirring method, and the viscosity of the slurry can be gradually increased to meet the appropriate process requirements.

[0016] Optionally, the step of printing the carbon fiber resistor slurry on the cured glass surface to prepare the strain resistor wire grid specifically includes: Select elastic elements made of 17-4PH material and perform cleaning and sandblasting; Applying glass slurry on the sandblasted surface of the elastic element; The elastic element is placed in a heating furnace and heated until the glass paste is completely solidified; The carbon fiber resistor slurry is printed on the cured glass surface according to the screen printing process; Continue to place the elastic element in the heating furnace, set the heating temperature to 480-520 degrees, and set the time to 20-30 minutes, until the organic components in the carbon fiber slurry are decomposed and volatilized to obtain the strain resistance wire grid.

[0017] By using 17-4PH stainless steel with excellent mechanical properties and being able to withstand greater stress, the surface contaminants of the elastic element are removed by sandblasting to obtain a surface with appropriate roughness. During the sintering process, on the one hand, after the carbon fiber is fully oxidized, the strength is reduced, but the activity is increased. On the other hand, the low-temperature glass powder will soften and penetrate into the gaps in the carbon fiber powder, filling the pores and forming a good bond.

[0018] The step can be continued by placing the elastic element in the heating furnace, setting the heating temperature to 480-520 degrees, and setting the time to 20-30 minutes, until the organic components in the carbon fiber slurry are decomposed and volatilized to obtain the strain resistance wire grid; the carbon fiber can be selectively oxidized before or after this step; The carbon fiber is fully oxidized by placing the elastic element in a heating furnace, setting the heating temperature to 400 degrees and the heating time to 2-3 hours.

[0019] Optionally, the glass paste is of the type Ferro, EG2964 or 2922, and is printed by screen printing.

[0020] Optionally, the step of connecting the strain resistance wire grids with conductive silver paste connecting wires and then connecting them with epoxy conductive silver glue to form a weighing sensor specifically includes: The strain resistance wire grid is connected with a conductive silver paste connecting wire. According to the specifications of the conductive silver paste, the curing temperature is set to 130°C and the insulation time is set to 30 minutes to improve its conductivity and stability.

[0021] Optionally, prepare a proper amount of epoxy conductive silver glue, fix one end of the enameled wire to the conductive silver paste electrical connection point through the epoxy conductive silver glue, and solder the other end to the pad of the terminal with an electric soldering iron to form a measuring bridge of the weighing sensor.

[0022] Compared with the prior art, the present invention has the following beneficial effects: 1. The manufacturing method of the weighing sensor based on conductive carbon fiber of the present invention adopts inorganic filling materials instead of organic polymer filling materials to form a new carbon fiber powder resistor slurry. The carbon fiber powder is oxidized and activated at high temperature, and is more tightly combined with the inorganic filling during the sintering process. The inorganic filling and the glass substrate are the same material, and the bonding of the resistor is more firm. The output signal of the sensor is larger than that of the metal strain gauge sensor, and the signal stability is improved compared with the carbon-based ink product.

[0023] 2. The manufacturing method of the weighing sensor based on conductive carbon fiber of the present invention can fully remove impurities on the surface of carbon fiber by placing the fiber powder in a glass container, making the powder drier and thus greatly improving its purity. The various components can be fully integrated through a segmented stirring method, and the viscosity of the slurry can be gradually increased to meet appropriate process requirements. The surface pollutants are removed by sandblasting the elastic element to obtain a surface with appropriate roughness. During the sintering process, on the one hand, after the carbon fiber is fully oxidized, although the strength is reduced, the activity is increased. On the other hand, the low-temperature glass powder will soften and penetrate into the gaps in the carbon fiber powder, filling the pores and forming a good bond. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a schematic diagram of the connection of the measuring bridge of the present invention; Figure 2 This is the frequency domain diagram of the signal-to-noise ratio of the traditional ink sensor under no-load; Figure 3 This is a frequency domain diagram of the signal-to-noise ratio of the sensor made by the method of the present invention under no-load. DETAILED DESCRIPTION

[0025] The present invention will be further described below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention. Embodiment 1

[0026] A method for preparing a carbon fiber resistor slurry using carbon fiber monofilaments is provided, comprising: A carbon fiber monofilament with a diameter range of 6 to 8 um composed of original fibers is selected, and the carbon fiber filament is ground into a fine powder with a length not exceeding 100 um by a ball mill. The rotation speed of the ball mill in this embodiment is preferably 200-300 rpm, and the grinding time is preferably set to 4 hours. At the same time, in order to avoid excessive wear, the mass ratio of the grinding ball to the carbon fiber is preferably 5 to 1. In this embodiment, the carbon fiber is preferably screened using multiple layers of sieves from coarse to dense, wherein the aperture of the sieve is preferably 150 um, 100 um, and 50 um to ensure that the powder length is uniformly less than 100 um.

[0027] It should be noted that in this embodiment, during the grinding process of the carbon fiber powder, it is necessary to prevent excessive crushing and agglomeration, and at the same time, the powder particle size is checked regularly to ensure that the grinding result meets the requirements.

[0028] The ground carbon fiber powder is mixed with an acetone solution. Specifically, the sieved carbon fiber powder is mixed with the acetone solution in a ratio of 1:5, and a mechanical stirring device is used to stir at a low speed for 10 minutes to preliminarily stir and disperse the powder. Then, a frequency of 40 kHz, a power of 150 W, and an oscillation time of 15-30 minutes are used to eliminate powder agglomeration and enhance the dispersibility of the carbon fiber. At the same time, impurities attached to the surface are removed to obtain a carbon fiber solution. The obtained carbon fiber solution is placed in a sealed glass vacuum cover, wherein a heating platform is built in the vacuum cover (the temperature is set to 50°C), and vacuuming is continued for 15 minutes. In this embodiment, the evaporation point of the solvent is reduced by heating and vacuum, and the removal of the acetone solution is accelerated to obtain a preliminarily cleaned carbon fiber powder.

[0029] The preliminarily cleaned carbon fiber powder is added to distilled water, mixed with a stirrer for 3 minutes, and then filtered. The washing is repeated until the pH value of the solution is close to neutral (pH is 6.5~7.0). The filtered carbon fiber powder is spread flat in a glass container, placed on a heating platform at 80°C, and the constant temperature drying time is set to 4 hours to ensure that the moisture and residual solvent are completely evaporated to obtain a carbon fiber powder with a clean surface.

[0030] Select clean carbon fiber powder (5-7 parts) that accounts for 15% of the total mass after sintering, 2-4 parts of low-temperature lead-free glass powder, 1-2 parts of diluent and 3-4 parts of anhydrous ethanol. The diluent in this embodiment is preferably 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate in the prior art. When stirring, use a magnetic stirrer at room temperature, set the speed to 600 rpm, set the stirring time to 2-6 hours, gradually increase the temperature to 85°C, adjust the stirring speed to 1000 rpm, and continue stirring until a carbon fiber resistor slurry with suitable viscosity is obtained.

[0031] In this embodiment, as the temperature rises, the solvent ethanol gradually evaporates and the slurry gradually reaches an ideal viscosity. The slurry viscosity is tested using a rotational viscometer to ensure that it is in the range of 5000-30000 cps (1 cps = 1 mPa·s). Too low viscosity may cause sagging during printing, while too high viscosity may reduce the uniformity of the coating.

[0032] When in use, the cleaning effect is improved by strictly controlling the number of cleaning times to ensure the neutral pH value of the final powder. By monitoring the stirring temperature and speed, the viscosity is measured in time after stirring and the diluent ratio is adjusted to ensure that the viscosity is within the set range. Embodiment 2

[0033] A method for preparing a strain resistance wire grid using carbon fiber resistance slurry is provided, comprising: The surface of the elastic element is pretreated, specifically including the selection of 17-4PH stainless steel, which has high strength, good corrosion resistance and dimensional stability, and can withstand long-term mechanical stress.

[0034] The elastic element is soaked in industrial ethanol or acetone for 10 minutes to remove grease, and an ultrasonic cleaning device (the frequency is preferably set to 40 kHz) is used to add deionized water and a detergent for cleaning for 5-10 minutes to remove oil, oxides and impurities on the surface of the elastic element, thereby providing a clean surface for subsequent sandblasting and coating processes. In this embodiment, after rinsing with deionized water, it is preferably dried in a drying oven at 80°C for 30 minutes.

[0035] The cleaned elastic element is sandblasted, preferably using alumina powder with a particle size of 50-100 μm, controlling the sandblasting pressure at 0.4-0.6 MPa, and preferably maintaining the sandblasting angle at 45 degrees to 60 degrees. Each part is sandblasted for 10-20 seconds to ensure that the surface roughness is within the range of Ra1.0~3.2μm, thereby increasing the surface roughness and improving the adhesion between the glass slurry and the elastic element. It should be noted that in this embodiment, the sand powder remaining on the surface should be blown away immediately with compressed air after sandblasting to avoid secondary contamination.

[0036] Select glass slurry of model Ferro EG2964 or 2922, use screen printing equipment, screen specification is 200 mesh, the glass slurry is printed on the sandblasted surface of the elastic element to ensure the uniformity of the coating. In this embodiment, the scraper angle of the coating process parameters is set to 45 degrees, the scraping speed is set to 75mm / s, and the coating thickness is controlled at 10-20um.

[0037] Place the elastic element in a heating furnace and heat it. Set the heating temperature to 550-600 degrees, the heating time to 15-20 minutes, and the heating rate to 10 degrees / min to avoid cracking or peeling of the glass layer due to too fast heating. At the same time, ensure that the temperature in the heating furnace is evenly distributed to avoid local overheating or insufficient temperature affecting the curing quality of the glass slurry.

[0038] Continue to use screen printing equipment with a screen specification of 300 mesh and scraping parameters consistent with the glass slurry coating process to print the carbon fiber slurry to ensure uniform thickness of the carbon fiber slurry coating and avoid local accumulation or missing. Pre-dry at 80°C for 10 minutes after each coating to improve the stability of the coating for subsequent high-temperature treatment.

[0039] The treated elastic element is placed in a heating furnace for heating, so that the organic binder and additives in the carbon fiber slurry are completely decomposed and volatilized at high temperature, and the glass component reaches the sintering temperature, thereby enhancing the mechanical and conductive properties of the wire grid. The heating temperature is set at 480-520°C, the setting time is 20-30 minutes, and the heating rate is controlled at 10°C / minute to prevent thermal shock of the material caused by sudden temperature changes, and to ensure that the maximum sintering temperature of the glass component in the carbon fiber slurry is lower than the sintering temperature of the previously solidified glass slurry by more than 50°C, so as to avoid interface mismatch leading to coating shedding.

[0040] In this embodiment, when the carbon fiber is fully oxidized, an optional step is to maintain the elastic element at 400 degrees for more than 2 hours, fully in contact with hot air, enhance the conductivity of the carbon fiber through high-temperature oxidation, and improve its adhesion to the substrate. This step can be targeted before or after the step of decomposing and volatilizing the organic components in the carbon fiber slurry.

[0041] When used, this method provides insulation and mechanical support functions. The carbon fiber slurry as a conductive layer achieves high sensitivity and stability in strain response, ensures that the thermal expansion coefficients of the glass layer and the carbon fiber layer match, and effectively prevents interface debonding or cracking after high-temperature treatment. Through multi-stage heating (400°C oxidation treatment, 480-520°C sintering treatment), the conductivity of the carbon fiber and the stability of the coating are enhanced. Embodiment 3

[0042] A method for preparing a weighing sensor based on strain resistance wire grid connection is provided, which specifically includes: The connection of the strain resistor wire grid is achieved by connecting the electrodes of the strain resistor wire grid to the enameled wire lead wire, specifically including: coating the wire grid electrode area with conductive silver paste to ensure uniform coverage, contacting one end of the enameled wire with the electrode covered with silver paste, placing it in a constant temperature furnace, setting the temperature to 130°C, keeping it for 30 minutes to allow the conductive silver paste to completely solidify, and checking the conductivity and connection firmness after cooling.

[0043] More preferably, in this embodiment, a silver paste with good conductivity and excellent curing performance is selected, preferably Ag-45, the enameled wire is preferably a high temperature resistant and bending resistant enameled copper wire, and the terminal is preferably a highly conductive metal material, such as a gold-plated copper terminal.

[0044] It should be noted that in this embodiment, when applying the silver paste, excessive accumulation should be avoided so as not to affect the conductivity and curing effect. During the curing process, the temperature should be uniform to prevent the contact points of the enameled wire from being damaged due to overheating.

[0045] Epoxy conductive silver glue is fixed by applying an appropriate amount of epoxy conductive silver glue on the connection point where the silver paste is cured, placing the connection point in a drying oven at 80°C for 2 hours. After curing, check whether the silver glue coverage is complete and there are no bubbles or degumming.

[0046] It should be noted that in this embodiment, the silver paste coating needs to cover the entire connection point and avoid affecting other electrode areas. The silver paste components need to be fully mixed before use to ensure uniform conductivity and adhesion properties.

[0047] The welding of the terminal block realizes the electrical connection of the signal output interface by welding the other end of the enameled wire to the pad of the terminal block, specifically including: using an electric soldering iron (the temperature is preferably set to 350°C) to strip off the insulating varnish layer at the end of the enameled wire, applying solder on the pad of the terminal block, contacting the exposed copper wire of the enameled wire with the pad, heating with an electric soldering iron to completely melt the solder, fixing the connection, and checking whether the solder joint is firm after cooling, and whether there is any false solder joint or cold solder joint.

[0048] It should be noted that in this embodiment, the temperature during the welding process should not be too high to avoid burning the enameled wire. The flux is used to improve the wettability of the solder joint, but the residual flux needs to be removed to prevent corrosion.

[0049] refer to Figure 1 As shown, the bridge in this embodiment uses 4 strain gauge wire grids connected in a Wheatstone bridge structure, and the 4 measuring arms are all strain-sensitive. The differential output is achieved by the Wheatstone bridge, which can eliminate part of the temperature drift effect. In the bridge: G1 and G3 both sense compressive strain (or tensile strain); G2 and G4 sense the opposite of G1 / G3. In this embodiment, the bridge is assembled by the following connection method.

[0050] Glue four wire grids symmetrically to appropriate positions of the elastic element (such as the surface of the bending area). According to the measurement requirements, correctly connect the electrodes and leads of the wire grids to form a bridge circuit. Debug the bridge, specifically: adjust the initial balance resistance value of the bridge (usually 350Ω) to ensure that zero signal is output when there is no external force, and test the sensitivity and nonlinear error of the bridge under loading.

[0051] The assembled bridge is packaged and protected to prevent the external environment (such as humidity, dust) from damaging the sensor and to improve service life and reliability. The packaging material in this embodiment is preferably epoxy resin or polyurethane resin with good insulation and waterproof properties.

[0052] During assembly, first place the assembled bridge and lead parts into the mold, inject the packaging material to ensure that no bubbles are generated, and place it in an 80°C drying oven for curing for 4 hours. After curing, check the integrity and surface finish of the packaging layer, and seal the connection line interface of the sensor to prevent short circuits in humid environments. More preferably, in this embodiment, a protective cover should be designed on the external structure of the packaging structure to avoid mechanical damage.

[0053] When in use, the combined connection of conductive silver paste and epoxy conductive silver glue not only ensures the electrical performance but also improves the mechanical firmness. The Wheatstone bridge structure is adopted to compensate for the temperature drift and linear error, and improve the accuracy and stability of the sensor. Through packaging and protection design, the sensor can operate stably in harsh environments such as high humidity and high temperature.

[0054] refer to Figure 2 and Figure 3 As shown, the signal-to-noise ratio frequency domain diagram of the traditional ink sensor under no-load and the signal-to-noise ratio frequency domain diagram of the sensor made in this embodiment under no-load are provided respectively. Compared with the experimental data, the data obtained in this embodiment has the advantage of smaller output signal noise relative to the traditional ink sensor.

[0055] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the enlightenment of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the purpose of the present invention and the claims, which all fall within the protection of the present invention.

Claims

1. A method for manufacturing a weighing sensor based on conductive carbon fiber, characterized in that: include: Using carbon fiber monofilaments to prepare carbon fiber powder; The obtained carbon fiber powder is used to prepare a carbon fiber resistor slurry with suitable viscosity; The carbon fiber resistor slurry is printed on the solidified glass surface to prepare the strain resistor wire grid; The strain resistance wire grids are connected through wires to form a measuring bridge of the weighing sensor.

2. The method for manufacturing a weighing sensor based on conductive carbon fiber according to claim 1, characterized in that: The method of preparing carbon fiber powder by using carbon fiber monofilaments specifically comprises: Grinding: Grind the carbon fiber filaments into carbon fiber powder with a length not exceeding 100um; Stirring: Mix and stir the carbon fiber powder and acetone solution, and then ultrasonically vibrate for 15-30 minutes to obtain a carbon fiber solution; Vacuuming: The obtained carbon fiber solution is vacuumed and then filtered to obtain carbon fiber powder.

3. The method for manufacturing a weighing sensor based on conductive carbon fiber according to claim 2, characterized in that: The step of preparing a carbon fiber resistor slurry with suitable viscosity from the obtained carbon fiber powder specifically comprises: The carbon fiber powder was placed in a glass container, distilled water was added, and the mixture was stirred and filtered. The process was repeated until the pH value of the solution was neutral. The filtered carbon fiber was placed in a heating device. The heating temperature was set to 80°C and the heating time was set to 4 hours. Impurities on the surface of the carbon fiber were removed to obtain a carbon fiber powder with a clean surface.

4. The method for manufacturing a weighing sensor based on conductive carbon fiber according to claim 3, characterized in that: Take 1-7 parts of cleaned carbon fiber powder, 2-4 parts of low-temperature lead-free glass powder, 1-2 parts of diluent, and 3-4 parts of anhydrous ethanol and mix them into a carbon fiber resistor slurry with appropriate viscosity.

5. The method for manufacturing a weighing sensor based on conductive carbon fiber according to claim 4, characterized in that: The mixing method includes: first stirring the mixture with a magnetic stirrer at room temperature, the stirring speed is 600 revolutions per minute, the stirring time is 2-6 hours, then setting the temperature to 85 degrees, adjusting the speed to 1000 revolutions per minute, and continuing to stir until the viscosity of the carbon fiber resistor slurry reaches 5000-30000cps.

6. The method for manufacturing a weighing sensor based on conductive carbon fiber according to claim 5, characterized in that: The step of printing the carbon fiber resistor slurry on the solidified glass surface to prepare the strain resistor wire grid specifically includes: Select elastic elements made of 17-4PH material and perform cleaning and sandblasting; Applying glass slurry on the sandblasted surface of the elastic element; The elastic element is placed in a heating furnace and heated until the glass paste is completely solidified; The carbon fiber resistor slurry is printed on the cured glass surface according to the screen printing process; Continue to place the elastic element in the heating furnace, set the heating temperature to 480-520 degrees, and set the time to 20-30 minutes, until the organic components in the carbon fiber slurry are decomposed and volatilized to obtain the strain resistance wire grid.

7. The method for manufacturing a weighing sensor based on conductive carbon fiber according to claim 6, characterized in that: The step continues with placing the elastic element in a heating furnace, setting the heating temperature to 480-520 degrees, and setting the time to 20-30 minutes, until the organic components in the carbon fiber slurry are decomposed and volatilized to obtain a strain resistance wire grid; carbon fiber oxidation can be selectively performed before or after this step; The carbon fiber is fully oxidized by placing the elastic element in a heating furnace, setting the heating temperature to 400 degrees and the heating time to 2-3 hours.

8. A method for manufacturing a weighing sensor based on conductive carbon fiber according to claim 6 or 7, characterized in that: The glass paste is of the type Ferro, EG2964 or 2922, and is printed by screen printing.

9. The method for manufacturing a weighing sensor based on conductive carbon fiber according to claim 8, characterized in that: The strain resistance wire grids are connected by conductive silver paste connecting wires and then connected by epoxy conductive silver glue to form a weighing sensor, specifically comprising: Use conductive silver paste connecting wire to connect the strain resistor wire grid. According to the specifications of the conductive silver paste, set the curing temperature to 130°C and the insulation time to 30 minutes.

10. The method for manufacturing a weighing sensor based on conductive carbon fiber according to claim 9, characterized in that: Prepare an appropriate amount of epoxy conductive silver glue, fix one end of the enameled wire to the conductive silver paste electrical connection point through the epoxy conductive silver glue, and use an electric soldering iron to solder the other end to the pad of the terminal to form the measuring bridge of the weighing sensor.

Citation Information

Patent Citations

  • Carbon-based conductive printing ink, and preparation method and applications thereof

    CN110105813A